Dinamika Pemerolehan dan Pembelajaran Bahasa dalam Perspektif Pendidikan Berkelanjutan - Sal Sabilla Ulayya Zahro; Zalzabila Wulandari; Lyra Rahma Wiratanayah Yusuf; M Yunus Abu Bakar (KAMPUS AKADEMIK PUBLISING, 2026)
This article reviews the dynamics of language acquisition and teaching from the perspective of continuing education. This study aims to analyze the differences in characteristics between children's language acquisition and adult language learning and their relationship to the development of lifelong education. The method used is qualitative research with a literature study approach through various relevant source analyses. The results of the study show that language acquisition occurs naturally, intuitively, and unconsciously, while language learning is formal, organized, and conscious. Age, motivation, environment, social interaction, and teaching methods influence the success of these processes. In the perspective of continuing education, language teaching must be structured in a contextual, communicative, and adaptive manner in order to develop students' linguistic competence, literacy, and character continuously throughout their lives.